Comparison of hemodynamic response of small dose ketamine versus midazolam as co- induction agent to propofol: a randomized double blind interventional study - Sunil Chauhan; Sandeep Kothari; Nitish Chaudhary; Kiwi Mantan (Creative Pharma Assent, 2023)
The Anaesthesiology Department at Sawai Man Singh Medical College carried out this study. For this, 60 ASA grade I and II patients undergoing planned general surgery were randomly assigned into two groups of 30 each, with Group KP (n=30) receiving injections of ketamine at 0.3 mg/kg and Group MP receiving injections of midozolam at 0.03 mg/kg and Propofol I.V. The main goal of the study was to find the best induction by analysing changes in hemodynamic indicators from baseline to various time points after induction. On the basis of the necessary induction dose and hemodynamic characteristics, the groups were contrasted. The strategy used was to present the categorical data as percentages and compare them between groups using the Chi square test. The mean and standard deviation of the quantitative data were displayed, and students' t-tests were used to compare them. According to the study described above, group MP saw a greater fluctuation in heart rate than did group KP, whose heart rate remained more constant during the anaesthetic time. Group MP's blood pressure dropped more quickly after induction compared to group KP. The ketamine group's blood pressure remained the most stable out of all the groups. Apnea, pain upon injection, and uncontrollable movements were absent in the KP group. Of all the groups, the ketamine-propofol group required the least induction dose. As a result, we came to the conclusion that pretreatment with ketamine at a dose of 0.3 mg/kg results in better hemodynamic stability and requires less propofol for induction than midazolam does. The ketamine-propofol group is therefore the best of the two groups, making it the optimum induction agent